Pengaruh Permainan Edukatif Digital Terhadap Hasil Belajar Siswa SD Negeri 0507 Latong - Irma Sari Daulay; Dede Hasibuan; Lia Arifah Hasibuan; Sakinah Hasibuan; Siti Amalia Pasaribu; Siti Azizah Nasution; Saima Henti Hasibuan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The background of this study stems from the low learning outcomes of students on fraction material at SD Negeri 0507 Latong, which is largely caused by teacher-centered instruction and the limited use of interactive digital media. This study aims to determine the effect of digital educational games on the learning outcomes of fifth-grade students. A quantitative approach was employed, with data collected through pretests, posttests, questionnaires, documentation, and interviews. Data were analyzed using simple linear regression. The findings show a significant increase in students’ posttest scores compared to their pretest results, along with positive student responses toward the use of digital educational games. The coefficient of determination of 52.5% indicates that digital media contributes strongly to improving learning outcomes. In conclusion, digital educational games are effective learning tools for enhancing students’ understanding of fractions and can serve as an innovative alternative to conventional teaching methods in elementary schools.